"BULLING" AS AN URGENT PROBLEM OF SOCIETY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article focuses on the problem of “bulling”, child-centered violence, and its prevention. Bulling is the use of violence, coercive behavior, derision or threat with offensive words, abuse of trust, aggression, or intimidation of dominance. This behavior is often repeated and commonplace.